1991
DOI: 10.1557/proc-250-291
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition of Copper Oxide Thin Films

Abstract: Copper oxide films were prepared by organometallic chemical vapor deposition of copper acetylacetonate in an oxygen-rich environment. The films were characterized by X-ray diffraction, Auger electron spectroscopy, X-ray photoelectron spectroscopy, and scanning electron microscopy. At 360 °C, Cu2O films were formed for an oxygen pressure of 150 torr and a copper acetylacetonate vapor pressure of 0.2 torr). The Cu2O film was polycrystalline, but the orientation was primarily [111]. Differential scanning calorime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Differential scanning calorimetry experiments on Cu-(acac)2 (Chang et al 35) indicated two different steps for the metal-ligand dissociation and the reaction between O2 and the ligand.…”
Section: Resultsmentioning
confidence: 99%